THE EUROPE OF ELITES: DIMENSIONS OF EUROPEANNESS OF POLITICAL AND ECONOMIC ELITES OF THE EU MEMBER STATES - Matonytė, Irmina; Morkevičius, Vaidas; Best, Heinrich (Politologija, 2015)
In this article we analyze the background and extent of the Europeanness of political and economic elites in the EU member states. The focus on the elites is based on the premise that European unification is still largely driven by the national elites of the EU member states. Europeanness of the elites is defined and operationalised along the lines of emotive, cognitive-evaluative, and projective dimensions. The emotive dimension is operationalized as the degree of the feeling of attachment to Europe reported by the elites. The cognitive-evaluative dimension is operationalized as the elite’s (positive) evaluation of the extent of the current European unification. Finally, the projective dimension is operationalized as elites’ support for a unified EU foreign policy in the future. We hypothesize about the relationships between dimensions of elites’ Europeanness and their ideologies, macro-contexts of life experiences, cultural and social capital as well as inter-elite cueing processes. We claim that the extent of elites’ Europeanness is related to 1) elites’ political views and ideologies, i.e. to the extremism of their political beliefs, that is, the more extreme right-wing or left-wing views are held by a representative of elite, the less European he or she is; 2) elites’ cultural capital, i.e. to their knowledge of foreign languages, that is the more languages a representative of elite speaks, the more European he or she is; 3) elites’ social capital, i.e. contacts with organisations and decision-making authorities at the European level, having relatives or close friends in other European countries or using foreign media for self-information, that is, the more contacts at the European level a representative of elite has, the more relatives or close friends in other European countries he or she has or the more frequently he or she uses foreign media for information, the more European he or she is; 4) inter-elite cueing, i.e. the extent of Europeanness of the counterpart elites, that is, the more European is a counterpart political elite, the more European is a representative of the economic elite and the more European is a counterpart national economic elite, the more European are representatives of national political elite; 5) macro-contexts of life experiences, i.e. gender, age and living in another European country, that is, women, younger elites and those having experience of living in another European country should be more pro-European. In order to test the hypotheses we use the data of interviews of political and economic elites in 17 EU member states collected in the IntUne (FP6) project. First, we reveal the diversity (contrary to a common premise of similarity) of national elites’ views and feelings toward the EU and Europe. However, this country-specific diversity does not overshadow the genuine link between different dimensions of Europeanness: the more European are elites on emotive or cognitive-evaluative dimension, the more European they also are on the projective dimension. We use regression analysis to test the proposed hypothetical relations between distinguished dimensions of elites’ Europeanness and their ideologies, macro-contexts of life experiences, cultural and social capital as well as inter-elite cueing processes. The results show that elites’ Europeanness depends on their ideological extremism: the more extreme the political beliefs of elites are, the less attachment they feel to Europe as well as the more frequently they report that European unification has already gone too far. Elites’ Europeanness also depends on their social and cultural capital: the more European languages representatives of elites speak the higher they score on emotive and projective dimensions of Europeanness. Similarly, the more frequently elites have contacts with organisations and authorities at the European level or if they have relatives or close friends in other European states, they are more pro-European on the emotive dimension. Moreover, the more frequently elites have contacts with organisations and authorities at European level or the more frequently they use foreign media for information, the higher is their cognitive-evaluative Europeanness. However, the strongest impact on elites’ Europeanness (on all the dimensions) is derived from the inter-elite cueing processes: the more European is a counterpart political elite, the more European are representatives of the economic elite and the more European is a counterpart economic elite, the more European are representatives of the political elite. Interestingly, macro-contextual effect on elites’ Europeanness is almost not existent, except for the relationship between older age and higher emotive Europeanness of elites. Concluding the article we sketch possible further directions of empirical investigation of elites’ Europeanness.